Ascochyta blight (Ascochyta fabae) of faba bean (Vicia faba L.): phenotypic and molecular characterization, pathogenicity and in vitro biological control by Bacillus spp. and Pseudomonas spp. - Oguiba, Bouchra; Karkachi, Noureddine; Suárez-Estrella, Francisca; Haouhach, Sadika; Kihal, Mebrouk; López, María J. (Archives of Biological Sciences, 2023)
Paper description: Ascochyta blight (Ascochyta fabae) is a major biotic constraint for faba bean (Vicia faba ) production worldwide. No information is available in the literature on local isolates from Algeria, and no studies on its biological control exist. 14 strains of fabae were isolated and identified by morpho-molecular characterization and the pathogenicity assay. Isolates were separated into three groups according to their level of aggressiveness. Bacillus siamensis B8 and Bacillus mojavensis B31 were the most effective against all isolates. fabae aggressiveness was negatively correlated with susceptibility to biocontrol strains. These findings have important implications for epidemiological studies and disease management. Abstract: Ascochyta blight is a major biotic constraint of faba bean (Vicia faba L.) production and productivity worldwide caused by Ascochyta fabae. No studies have been performed in Algeria to identify A. fabae isolates or to assess their pathogenicity, and therefore information on local isolates is insufficient. Herein, 14 isolates of A. fabae were obtained from faba bean samples and identified based on morphological traits and phylogenetic analysis of internal transcribed spacer sequences. All generated sequences have been deposited in GenBank and assigned accession numbers. Pathogenicity tests on faba bean plants revealed that all isolates produced necrotic lesions on aerial parts with variable intensity, classifying them as weakly, moderately, and highly aggressive. The in vitro antifungal activity of Bacillus and Pseudomonas strains against A. fabae isolates showed that Bacillus siamensis B8 and Bacillus mojavensis B31 had the highest suppressive potential against all isolates. Moreover, a negative correlation was found between the aggressiveness of A. fabae isolates and their susceptibility to biocontrol strains. This is the first report on the identification, pathogenicity and in vitro biological control of A. fabae isolates in Algeria. B8 and B31 could be further developed as promising biocontrol agents for the control of the ascochyta blight of faba bean.